Perlindungan Hukum Terhadap Konsumen Perjanjian Pinjaman Online berdasarkan Undang-Undang Nomor 8 Tahun 1999 - Renni Junita Br Perangin Angin; Elvira Fitriyani Pakpahan; Rizki Rizki; Adella Sitanggang; Widodo Ramadhana (Jurnal Hukum Lex Generalis, 2025)
.The development of information technology has significantly transformed the financial sector, including the emergence of online lending services. However, the widespread use of online loan agreements is often accompanied by practices that harm consumers, such as high interest rates, misuse of personal data, and threats or intimidation during the debt collection process. This research aims to analyze the legal protection of consumers in online loan agreements based on Law Number 8 of 1999 concerning Consumer Protection. This study employs normative legal research using statutory and conceptual approaches. The discussion results indicate that Law Number 8 of 1999 provides both preventive and repressive protections to consumers, including the right to comfort, security, and safety in using services, as well as the right to accurate information. Nevertheless, its implementation still faces challenges due to low digital literacy among the public and weak supervision of illegal online lending providers. The conclusion of this research is that legal protection for consumers in online loan agreements is normatively regulated, but still requires stronger law enforcement, public education, and regulatory improvement to ensure optimal consumer protection.